Copper-Tannate Complexes As Antifoulant In Antifouling Paint For Fish-Cage Nets - Usol Ghafli, Nurul Azwin (2014)
Tannin extracted from mangrove bark, Rhizophora apiculata (R. apiculata) was used as a natural-origin source to be complexed with copper(U) salt. The copper-tannate (Cu-T) produced was used as an antifoulant in antifouling paint. Mangrove bark was extracted using 70% (v/v) aqueous acetone and gives 31.1 % extraction yield. The total phenolic content (TPC) of mangrove tannin extract (MT) was 186.0 mg gallic acid equivalent per gram sample, total flavonoid content (TFC) was 96.0 mg catechin equivalent per gram sample and condensed tannin content (CTC) was 95.5% weight content. The optimum condition of copper-tannate complexes (Cu-T) was studied using precipitation curve on varies parameters which were copper dosage, reaction temperature, reaction time and pH of Cu-T solution. The optimum conditions were taking into account of Cu-T percentage yield and IR spectrum analysis. Three derivatives ofCu-T at different pH, which were Cu-T pH 3.5, Cu-T pH 5.0 and Cu-T pH 8.0, were chosen for further analysis. The concentration of copper element in CuT and commercialized antifoulant, Cu-Oma was measured using AAS analysis and shown that Cu-T complexes had lower amount of copper content which are almost 50% lower than Cu-Oma.